THE LEVEL OF FAMILY KNOWLEDGE ABOUT RELAPSE PREVENTION IN PATIENTS WITH MENTAL DISORDERS IN THE NUSA INDAH WARD AT DR. SOEDOMO HOSPITAL, TRENGGALEK - Novia Arinanda, Sandy; Yulidaningsih, Elok; Bahari, Kissa (Lux Mensana: Journal of Scientific Health, 2025)
Introduction. Relapse in mental disorder patients can be caused by the family, even the family still does not understand how to prevent recurrence. The general aim of this research is to determine the level of family knowledge about preventing relapse in patients with mental disorders in the knowledge domain (C1) and the level of family knowledge about preventing relapse in patients with mental disorders in the domain of understanding (C2). Methods. This study used a descriptive quantitative research design to describe the level of family knowledge about relapse prevention in patients with mental disorders. The study population consisted of 12 respondents, and the sample size was 10 respondents, selected using purposive sampling. The instrument used in this study was a questionnaire. Data analysis was conducted descriptively. Result&Analysis. The majority of families of mental disorder patients have sufficient and insufficient knowledge regarding relapse prevention. The level of family knowledge about preventing relapse in patients with mental disorders in the knowing domain (C1) and the level of family knowledge about preventing relapse in patients with mental disorders in the knowing domain (C2) are the same. included in the categories of sufficient and insufficient. Discussion. To reduce the risk of relapse in mental health patients, it is important for families to increase knowledge about preventive measures and understand early warning signs.